Survey of periodicals 1976 - Olsson, Claes-Olof (University of Gothenburg, 1982)
The aim of this study was to classify periodicals into different groups. The data file includes information on the name of the periodical, organization behind, year established, number of publications per year, circulation figures, subscription fees, Printed Matter Rate, edition distributed by post, and weight.

Purpose:

Classify periodicals into different groups

Studien innehåller bland annat uppgifter om tidskriftens namn , vilken organisation tidskriften är organ för, etableringsår, utgivningsfrekvens, upplaga, prenumerationspris, antalet postdistribuerade tidningsexemplar.

Syfte:

Klassificera tidskrifter i olika grupper
Tidskriftsundersökningen 1976
Keywords: mass media; massmedia; periodicals readership; tidskrifts läsekrets; organizations; organisationer; Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap